Soils of the Caribbean - Ahmad, N. (Technical Centre for Agricultural and Rural Cooperation, 2011)
Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.Professor Ahmad’s comprehensive survey and detailed analysis of the soils of the Caribbean region is a pioneering effort to address sporadic and deficient research on the subject. The proper use of the soils of the Caribbean is critical to food security, export of agricultural products and in the provision of housing, tourism and industrial development, and sports and recreational facilities. Identifying common features of the soils and their management, this book also presents detailed studies of the soils of each of the countries of the Caribbean. Incorporating the geology, relief, climate and vegetation of the region, the text is supplemented by numerous maps, figures, tables and photos. The title provides a unique source of original research that will be invaluable to researchers, practitioners and students.